How to age disgracefully [large type] - Pooley, Clare (Thorndike Press large print dynamic drama., 2024)
"When Lydia takes a job running the Senior Citizens' Social Club three afternoons a week, she assumes she'll be spending her time drinking tea and playing gentle games of cards. The members of the Social Club, however, are not at all what Lydia was expecting. From Art, a failed actor turned kleptomaniac to Daphne, who has been hiding from her dark past for decades to Ruby, a Banksy-style knitter who gets revenge in yarn, these seniors look deceptively benign--but when age makes you invisible, secrets are so much easier to hide. When the city council threatens to sell the doomed community center building, the members of the Social Club join forces with their tiny friends in the daycare next door--as well as the teenaged father of one of the toddlers and a geriatric dog--to save the building. Together, this group's unorthodox methods may actually work, as long as the police don't catch up with them first"--